Photosynthesis in Bryophytes and Early Land Plants - Hanson, David T.; Rice, Steven K. (Advances in Photosynthesis and Respiration, Including Bioenergy and Related Processes,, 2014)
Bryophytes, which are important constituents of ecosystems globally and often dominate carbon and water dynamics at high latitudes and elevations, were also among the pioneers of terrestrial photosynthesis.  Consequently, in addition to their present day ecological value, modern representatives of these groups contain the legacy of adaptations that led to the greening of Earth.  This volume brings together experts on bryophyte photosynthesis whose research spans the genome and cell through whole plant and ecosystem function and combines that with historical perspectives on the role of algal, bryophyte and vascular plant ancestors on terrestrialization of the Earth.  The volume begins with an overview of what can be learned from bryophyte photosynthesis followed by the consideration of fossil, biogeochemical, systematic and comparative physiological evidence to understand three phases of terrestrialization:  the transition to land from aquatic algal ancestors, the physiological adaptation of early land plants, and the diversification of plants and environments.  Then the volume introduces new perspectives and reviews photosynthetic physiology across spatial and temporal scales in seven chapters that focus on the unique strategies of bryophytes in relation to genomics, carbon acquisition, chloroplast movement, photoprotection and canopy structure and on novel approaches to investigating bryophyte photosynthesis.  After these perspectives, the volume emphasizes the ecological setting, showing how the photosynthetic physiology of bryophytes plays out within aquatic, peatland, tropical, dryland and Antarctic settings with discussions of implications of global change.  Finally, the volume ends with a discussion of opportunities in bryophyte photosynthesis research and some useful resources. Overall, the eighteen well-illustrated chapters reveal unique physiological approaches to achieving carbon balance and dealing with environmental limitations and stresses that present an alternative, yet successful strategy for land plants. .